2016
DOI: 10.1016/j.jtcvs.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet versus oral anticoagulant therapy as antithrombotic prophylaxis after mitral valve repair

Abstract: Vitamin K antagonist therapy was not superior to antiplatelet therapy to prevent thromboembolic complications after mitral valve repair. Our data suggest that oral anticoagulation may carry a higher bleeding risk compared with antiplatelet therapy, although these results should be confirmed in an adequately powered randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…The observed 3-month cumulative incidence for thromboembolic events is in aligned with those reported by previous studies [ 4 , 18 ]. The observed incidence of major bleeding events was slightly higher than described in previous reports, probably due to the adjudication process of postoperative pericardial tamponade [ 19 , 20 ]. Pericardial effusion alongside signs of hemodynamic instability was adjudicated as a pericardial bleeding, whereas these events might not be considered as (major) bleedings in previous studies.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The observed 3-month cumulative incidence for thromboembolic events is in aligned with those reported by previous studies [ 4 , 18 ]. The observed incidence of major bleeding events was slightly higher than described in previous reports, probably due to the adjudication process of postoperative pericardial tamponade [ 19 , 20 ]. Pericardial effusion alongside signs of hemodynamic instability was adjudicated as a pericardial bleeding, whereas these events might not be considered as (major) bleedings in previous studies.…”
Section: Discussioncontrasting
confidence: 59%
“…Recommendations from international guidelines are contradictory to our results, favouring either VKA or aspirin as postoperative thromboprophylaxis 3 months after MVr [ 5 , 6 , 21 ]. Three former retrospective studies have compared antiplatelet with anticoagulation therapy in patients after MVr [ 8 , 19 , 20 , 22 ]. Two studies found no differences in stroke and bleeding rate of early VKA treatment compared with aspirin therapy, suggesting that VKA treatment might not be necessary [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticoagulation after mitral valve replacement (MVR) is intended to reduce clot formation on new prosthetic material and suture lines, and in turn reduce the risk of thromboembolism until the prosthetic material is fully endothelialized, a process that generally takes 3 months. 1,3 Mitral valve surgery has been associated with increased short-term risk of thromboembolic incidents after surgery, with an incidence of ischemic stroke within the first 30 postoperative days reported to be 4.6% ± 1.5% for MVR with a biological prosthesis, 1.5% ± 0.4% for mitral valve repair (MVr), and 1.3% ± 0.8% for a mechanical prosthesis. 4 In addition, roughly one-third of patients undergoing mitral valve surgery will experience atrial fibrillation postoperatively, which has been associated with increased risk of stroke and early death and further supports the use of anticoagulation for thromboembolic prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Management of patients with valve repair necessitates antithrombotic therapy for the first 3 months following surgery [ 21 ], which is a high-risk period for thromboembolism. Anticoagulation therapy has no extra advantage over antiplatelet therapy in valve repair patients, and anticoagulation therapy may lead to major bleeding complications [ 22 ]. Nonetheless, the efficacy of anticoagulants in patients with valve repair needs to be confirmed in randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%